Rapid formation of an ice doline on Amery Ice Shelf, East Antarctica - Roland Warner; Fricker, HA; Adusumilli, S; Arndt, P; Kingslake, J; Spergel, JJ (2021)
Surface meltwater accumulating on Antarctic ice shelves can drive fractures through to the ocean and potentially cause their collapse, leading to increased ice discharge from the continent. Implications of increasing surface melt for future ice shelf stability are inadequately understood. The southern Amery Ice Shelf has an extensive surface hydrological system, and we present data from satellite imagery and ICESat-2 showing a rapid surface disruption there in winter 2019, covering ∼60 km 2 . We interpret this as an ice-covered lake draining through the ice shelf, forming an ice doline with a central depression reaching 80 m depth amidst over 36 m uplift. Flexural rebound modeling suggests 0.75 km 3 of water was lost. We observed transient refilling of the doline the following summer with rapid incision of a narrow meltwater channel (20 m wide and 6 m deep). This study demonstrates how high-resolution geodetic measurements can explore critical fine-scale ice shelf processes.